2008
DOI: 10.1093/ndt/gfn521
|View full text |Cite
|
Sign up to set email alerts
|

Serum  2-microglobulin level is a significant predictor of mortality in maintenance haemodialysis patients

Abstract: Background. β 2 -Microglobulin (β 2 -M) is recognized as a surrogate marker of middle-molecule uraemic toxins and is a key component in the genesis of dialysis-associated amyloidosis. Few studies have evaluated the association of β 2 -M levels with clinical outcome in dialyzed patients. Methods. The prognostic implication of serum β 2 -M levels for the survival of haemodialysis patients was examined in 490 prevalent haemodialysis patients (60.1 ± 11.8 years, haemodialysis duration of 87.4 ± 75.7 months, 288 ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
110
1
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(122 citation statements)
references
References 34 publications
5
110
1
5
Order By: Relevance
“…18 In patients on HD, serum b 2 M is markedly increased and predicts all-cause mortality, 19,20 but studies on the relationship between serum b 2 M and cardiovascular disease are limited. It has been reported that serum b 2 M correlates with carotid IMT 21 and the number of calcified valves.…”
Section: Discussionmentioning
confidence: 99%
“…18 In patients on HD, serum b 2 M is markedly increased and predicts all-cause mortality, 19,20 but studies on the relationship between serum b 2 M and cardiovascular disease are limited. It has been reported that serum b 2 M correlates with carotid IMT 21 and the number of calcified valves.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the Hemodialysis (HEMO) study, we used 20 mL/h/mmHg as the cutoff point to differentiate low and high flux. 3 Our patients began the study by receiving dialysis on a NIPRO 130G (low-flux, Osaka, Japan) dialyzers for at least two years and were then changed to FX60 (highflux, Fresenius, Bad Homburg, Germany) dialyzers for three years. The performance and technical data of the NIPRO 130G (Nipro, Osaka, Japan) and FX60 (Fresenius, Bad Homburg, Germany) are summarized in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…In hemodialysis (HD) patients, serum ␤2M levels may be increased by 20-fold or more as compared with the general population, the highest levels being observed in patients without residual kidney function (RKF) (4)(5)(6). It has been shown that predialysis ␤2M levels predict all-cause and infectious-related mortality in these patients (4,7,8).…”
mentioning
confidence: 99%